Assessing the Indonesian National Police Crisis Communication in the Ferdy Sambo Case: Media Strategy, Online Engagement, and SOSTAC Model Evaluation - Suspaningrum, Dewi; Sunarto (CHANNEL: Jurnal Komunikasi, 2024)
This study aims to evaluate the crisis communication strategies used by the Indonesian National Police to manage the high-profile Ferdy Sambo case, which negatively impacted the institution's reputation and public trust. By analyzing media coverage from August 2022 to March 2023, this research employs a post-positivistic paradigm and qualitative methods, including interviews with key personnel, to understand how the Indonesian National Police executed its crisis communication strategy. A summative evaluation approach is also used to assess the effectiveness of these efforts through public feedback, media responses, news analysis from kompas.com, and internal evaluations. Additionally, the study explores the role of internal organizational communication in aligning management actions with institutional objectives. The findings reveal both strengths and limitations in the strategies the Indonesian National Police applied, highlighting successful approaches used to repair and improve public perceptions of the institution, with the importance of transparency, rapid responsiveness, and consistency in communication. This study concludes with recommendations to enhance public relations practices, such as press or media relation strategy to sustain and build the institution’s reputation.